2022
DOI: 10.1128/iai.00059-22
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Proteolysis of an Essential Virulence Determinant Dictates Infectivity of Lyme Disease Pathogens

Abstract: The Borrelia burgdorferi BB0323 protein undergoes a complex yet poorly defined proteolytic maturation event that generates N-terminal and C-terminal proteins with essential functions in cell growth and infection. Here, we report that a borrelial protease, B. burgdorferi high temperature requirement A protease (BbHtrA), cleaves BB0323 between asparagine (N) and leucine (L) at positions 236 and 237, while the replacement of these residues with alanine in the mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The Borrelia burgdorferi HtrA, BbHtrA, is a therapeutic target shown to contribute to borrelial dissemination in the host and the pathogenesis of Lyme disease 15,19–22 . Interestingly, B. burgdorferi codes for only a single copy of the protein, enhancing its tractability as a drug discovery target 15,23–25 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Borrelia burgdorferi HtrA, BbHtrA, is a therapeutic target shown to contribute to borrelial dissemination in the host and the pathogenesis of Lyme disease 15,19–22 . Interestingly, B. burgdorferi codes for only a single copy of the protein, enhancing its tractability as a drug discovery target 15,23–25 .…”
Section: Introductionmentioning
confidence: 99%
“…The Borrelia burgdorferi HtrA, BbHtrA, is a therapeutic target shown to contribute to borrelial dissemination in the host and the pathogenesis of Lyme disease. 15,[19][20][21][22] Interestingly, B. burgdorferi codes for only a single copy of the protein, enhancing its tractability as a drug discovery target. 15,[23][24][25] Prior works characterizing the BbHtrA protein have shown that the proteolytically inactive S226A mutant elutes with co-purifying peptides, making it an ideal validation target for the workflow.…”
mentioning
confidence: 99%
“…The B. burgdorferi HtrA, BbHtrA, is a therapeutic target shown to contribute to borrelial dissemination in the host and the pathogenesis of Lyme disease (Kariu, Yang et al 2013, Kariu, Sharma et al 2015, Ullmann, Russell et al 2015, Russell, Tang et al 2016, Thakur, Bista et al 2022). Interestingly, B. burgdorferi codes for only a single copy of the protein, enhancing its tractability as a drug discovery target (Gherardini 2013, Russell, Delorey et al 2013, Russell, Tang et al 2016, Ye, Sharma et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The Borrelial high temperature requirement A (BbHtrA) protein is a member of the HtrA family, a group of proteases widely expressed across the animal kingdom and essential to the survival and infectivity of a number of microbes of concern to public health ( Pallen and Wren, 1997 ; Clausen et al, 2002 ; Krojer et al, 2002 ; Ibrahim et al, 2004 ; Zurawa-Janicka et al, 2010 ; Clausen et al, 2011 ; Backert et al, 2018 ; Cho et al, 2020 ). BbHtrA is a therapeutic target of interest in Borrelia burgdorferi due to its involvement in borrelial invasion and dissemination in the human host and may play a role in late-stage symptoms of Lyme disease ( Gherardini, 2013 ; Kariu et al, 2013 ; Russell et al, 2013 ; Stricker and Johnson, 2013 ; Kariu et al, 2015 ; Ye et al, 2016 ; Zhuang et al, 2018 ; Bernard et al, 2019 ; Thakur et al, 2022 ). In this manuscript, we describe the application of a fluorophore, linked to the protein of interest via an affinity tag, that results in a more agnostic, specific signal in a DSF setting, as well as the optimization and production of 384- and 1536-well assays to screen for small molecule binders to HIS-tagged BbHtrA.…”
Section: Introductionmentioning
confidence: 99%